2001
DOI: 10.1597/1545-1569(2001)038<0231:rasiaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency and Success in Adults With Moebius Syndrome

Abstract: The recognition and reinforcement of strengths and resiliences in younger patients may help maximize their professional and personal success as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 15 publications
9
39
0
Order By: Relevance
“…Determination has previously been related to better adjustment to chronic illness (e.g. Lo and MacLean, 2001) and, in the disfigurement literature, Meyerson (2001) identified it as a way of bolstering resilience.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Determination has previously been related to better adjustment to chronic illness (e.g. Lo and MacLean, 2001) and, in the disfigurement literature, Meyerson (2001) identified it as a way of bolstering resilience.…”
Section: Discussionmentioning
confidence: 94%
“…Thompson and Broom (2009) also refer to specific types of humour used in relation to coping with a visible difference, namely sarcasm, understatement and self-deprecation. Other disfigurement research has identified humour as a source of resilience and strength (Meyerson, 2001). More generally, 'coping humour' has been described as the use of humour to manage a situation that threatens one's usual pattern of living (Martin, 1996) and it is thought to help diffuse emotions in adverse circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we recommend that people with MoS take on the responsibility to educate others people who might play important roles in their lives. Educating others gives the person with MoS control over the situation, allows them to manage others' impressions, raise awareness, and can make both parties feel more comfortable (Egan et al, 2011;Meyerson, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Through focus groups and interviews with resilient individuals with visible difference, Egan et al (2011) found themes of importance of appearance, personal growth, relationships with others, and coping. Similarly Meyerson (2001) examined resiliency and success in adults with MoS and identified factors leading to resiliency and success: humor, determination to surpass others' lowered expectations of them, sense of self, special skills, family support, networking, and faith.…”
mentioning
confidence: 99%